Korelasi Kitab Silsilah al-Aḥādīts al-Ṣaḥīḥah dan Silsilah al-Aḥādīts al-Dha’īfah wa al-Mawdhū’ah Karya Muḥammad Nāṣir Al-Dīn Al-Albānī - Abustani Ilyas (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2008)
This article studies about correlation of two books under the title Silsilah al-Ḥadīts al-Ṣaḥīḥah and Silsilah al-Ḥadīts al-Dha’īfah wa al-Mawdhū’ah, masterpieces of Muḥammad Nāṣir Al-Dīn Al-Albānī, by using comparative and content analysis methods. Two books represent collection of hadith which vary its qualities: sahih, hasan, daif, even maudhu’, without engagement with certain chapter or title. The difference among both lay in the methods used in mean region of hadith and philosophy affect numbers of hadith which are daif in quality.